NEGOTIATION OF IDENTITY IN DIASPORIC LITERATURE: A CASE STUDY ON AMY TAN’S THE HUNDRED SECRET SENSES AND LESLIE MARMON SILKO’S CEREMONY - Ken Ruri Nindyasmara (Rubikon : Journal of Transnational American Studies, 2016)
Negotiation of identity has become an important issue because its never-ending process always relates to conflicts, differences and similarities. Chinese Americans and Native Americans are two distinct diasporic communities amongst other ethnic group in the U.S. As minorities, they experience prejudice, discrimination and exclusion from mainstream American culture and society. This research aims to reveal the negotiation of identity of Chinese Americans and Native Americans which is reflected on their literature. Literature is seen as the record of diasporic experience of both ethnic groups. This research is qualitative conducted under Post-Nationalist American Studies. Post-colonial, hegemony and representation theories are used to help the process of data analysis. The primary data is taken from The Hundred Secret Senses written by Amy Tan and Ceremony written by Leslie Marmon Silko. The secondary data are taken from books, journals, and internet sources. The finding of the research shows that Chinese Americans and Native Americans negotiate their identity by choosing or combining competing values. The construction of identity is done through the reenactment of ethnic root and the adaptation to mainstream American cultural values. Sense of belongingness, history and socio-cultural background become the determining factors of identity negotiation. In brief, they construct hybrid identity to survive and to counter American hegemony. Compared to Native Americans, Chinese Americans are more blending to mainstream American culture. However, both novels depict their hybrid identity. Keywords: identity negotiation, diasporic literature, diaspora communities, hegemony, hybrid identity